Literature Study : Activity-Based Costing System - Setyaning, Larashati B'tari; Fara Dita, Andriani Okta (Institut Teknologi Adhi Tama Surabaya, 2020)
Increasing competition forces companies to be competitive. Competitiveness can be achieved by conveying product value to consumers at low prices. To achieve this, a good cost approach is needed, one of which is the Activity-Based Costing System (ABC). In this literature study the authors divide ABC into 3 parts, namely the concept of ABC, the stages in ABC and the costs and benefits of implementing ABC. ABC is a cost approach method by calculating the cost of activities to produce products, both goods and services where these activities require resources. After conducting a literature study, the authors found similarities and inequalities among several literatures and then draw conclusions. The conclusion that can be drawn is that the ABC system is used by companies to get more accurate production costs, accurate production costs can increase company profits and the criteria for companies that are suitable for using the ABC system are companies with a high level of product diversity, there is intense competition with companies that produce similar products, as well as the cost of implementing the ABC system is low.